2019
DOI: 10.3390/bs9050046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Intention to Use the Common Ticketing System (Spider Card) in Thailand

Abstract: The Common Ticket, locally called the “Spider Card” is a contactless smartcard ticket used for public transportation systems in Thailand. The card is used for all modes of transportation and increases the convenience of public transit passengers while increasing public transport ridership. This research aimed to identify the determinant factors that impact passengers’ intention to use the Spider Card based on the unified theory of acceptance and use of technology (UTAUT) model by integrating perceived convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…On the contrary, Prayoonphan and Xu revealed that SI did not impact passengers' intention to use smartcard ticket in Thailand [47]. Mensah observed interesting results on the study related to e-government services in China.…”
Section: Social Influencementioning
confidence: 93%
“…On the contrary, Prayoonphan and Xu revealed that SI did not impact passengers' intention to use smartcard ticket in Thailand [47]. Mensah observed interesting results on the study related to e-government services in China.…”
Section: Social Influencementioning
confidence: 93%
“…This integrated model is then called the combined theory of technology acceptance and use (UTAUT). [37] The main determinant influences the intended use effect from the perspective of new technology, which can be determined by three constructs including performance expectations, business expectations, and social influence. Performance expectations are defined as the extent to which a person believes that using the system will help them achieve results in job performance [35], while business expectations can be defined as the level of comfort associated with the use of technology by consumers which explains the individual's perception of the level of difficulty or ease of using IT systems [35] as well as being a predictor for individual intentions to use IT [38].…”
Section: Adoption Technology Theorymentioning
confidence: 99%
“…The results showed that most of the UTAUT constructions had a strong positive influence on behavioral intention. Facilitation conditions as one of the determining factors that influence the intention to use Spider Cards and have a positive influence on technology adoption and intentions [39] [37]. In general, UTAUT focuses on the intensity of the use of technology in terms of human behavior.…”
Section: Adoption Technology Theorymentioning
confidence: 99%
“…The model includes approximate path coefficients indicating the hypothesized correlation's strength and the R-square value determining the model's predictive strength. Path coefficients (β value and significance) and R-square show how well the data support the hypothesized model [26]. Figure 1 and Table 7 illustrate the structural model results from the PLS-SEM output.…”
Section: Structural Model Assessmentmentioning
confidence: 81%